KEBIJAKAN DAN STRATEGI PENGEMBANGAN KAWASAN AGROEKOWISATA KECAMATAN TUTURDI KABUPATEN PASURUAN - Tjahjono, Jojok Dwirido; Maroeto, '; Edi Sasongko, Purnomo; Arifin, A. Zainul (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
This policy and strategy study based on the three indicators that are reviewed by the author is that the agroecotourism area structuring indicator which is the assessment item is the division of regional functions, land allotment, circulation and liaison and infrastructure development can be said to be less well implemented or the results of the study are based the initial concept can be said to fail in achieving the desired target. This is also based on supporting and inhibiting factors. As a supporting factor is the government policy of Pasuruan Regency based on RPJMD 2013-2018 and also the potential of the region and natural resources of Tutur District. Then the obstacle is the limited regional finances, lack of support from government apparatus and bureaucracy, structural and cultural constraints, socio-economic limitations and limited human resources.